Serological testing for Lyme Borreliosis in general practice: A qualitative study among Dutch general practitioners. (16th December 2020) - Vreugdenhil, Tjitske M.; Leeflang, Mariska; Hovius, Joppe W.; Sprong, Hein; Bont, Jettie; Ang, C. W.; Pols, Jeanette; Van Weert, Henk C. P. M.
Abstract: Background: Concerns are raised about missed, delayed and inappropriate diagnosis of Lyme Borreliosis. Quantitative descriptive studies have demonstrated non-adherence to the guidelines for testing for Lyme Borreliosis. Objectives: To gain insight into the diagnostic practices that general practitioners apply for Lyme Borreliosis, their motives for ordering tests and how they act upon test results. Methods: A qualitative study among 16 general practitioners using semi-structured interviews and thematic content analysis. Results: Five themes were distinguished: (1) recognising localised Lyme Borreliosis and symptoms of disseminated disease, (2) use of the guideline, (3) serological testing in patients with clinically suspect Lyme Borreliosis, (4) serological testing without clinical suspicion of Lyme Borreliosis, and (5) dealing with the limited accuracy of the serological tests. Whereas the national guideline recommends using serological tests for diagnosing, general practitioners also use them for ruling out disseminated Lyme Borreliosis. Reasons for non-adherence to the guideline for testing were to reassure patients with non-specific symptoms or without symptoms who feared to have Lyme disease, confirmation of localised Lyme Borreliosis and routine work-up in patients with continuing unexplained symptoms. Some general practitioners referred all patients who tested positive to medical specialists, where others struggled with the explanation of the results. Conclusion: Both diagnosis and ruling out of disseminated Lyme Borreliosis can be difficult for general practitioners. General practitioners use serological tests to reassure patients and rule out Lyme Borreliosis, thereby deviating from the national guideline. Interpretation of test results in these cases can be difficult.